Tenofovir disoproxil fumarate in pregnancy for prevention of mother to child transmission of hepatitis B in a rural setting on the Thailand-Myanmar border: a cost-effectiveness analysis - Marieke Bierhoff; Chaisiri Angkurawaranon; Marcus J. Rijken; Kanlaya Sriprawa; Pachinee Kobphan; Francois N. Nosten; Michèle van Vugt; Rose McGready; Angela Devine (BMC, 2021)
Abstract Background Hepatitis B Virus (HBV) is transmitted from mother to child which can be prevented via birth dose vaccine combined with three follow up hepatitis B vaccines, hepatitis B immunoglobulins (HBIG), and maternal antiviral treatment with Tenofovir Disoproxil Fumarate (TDF). This study evaluates the cost effectiveness of six strategies to prevent perinatal HBV transmission in a resource limited setting (RLS) on the Thailand-Myanmar border. Methods The cost effectiveness of six strategies was tested by a decision tree model in R. All strategies included birth and follow up vaccinations and compared cost per infection averted against two willingness to pay thresholds: one-half and one gross domestic product (GDP) per capita. Strategies were: 1) Vaccine only, 2) HBIG after rapid diagnostic test (RDT): infants born to HBsAg+ are given HBIG, 3) TDF after RDT: HBsAg+ women are given TDF, 4) TDF after HBeAg test: HBeAg+ women are given TDF, 5) TDF after high HBV DNA: women with HBV DNA > 200,000 are given TDF, 6) HBIG & TDF after high HBV DNA: women with HBV DNA > 200,000 are given TDF and their infants are given HBIG. One-way and probabilistic sensitivity analyses were conducted on the cost-effective strategies. Results Vaccine only was the least costly option with TDF after HBeAg test strategy as the only cost-effective alternative. TDF after HBeAg test had an incremental cost-effectiveness ratio of US$1062; which would not be considered cost-effective with the lower threshold of one-half GDP per capita. The one-way sensitivity analysis demonstrated that the results were reasonably robust to changes in single parameter values. The PSA showed that TDF after HBeAg test had an 84% likelihood of being cost effective at a willingness to pay threshold of one GDP per capita per infection averted. Conclusions We found that TDF after HBeAg test has the potential to be cost-effective if TDF proves effective locally to prevent perinatal HBV transmission. The cost of TDF treatment and reliability of the RDT could be barriers to implementing this strategy. While TDF after RDT may be a more feasible strategy to implement in RLS, TDF after HBeAg test is a less costly option.